Sex differences in behavior, immune function, and redox state throughout life, and their effect on the longevity of Swiss mice - Félix, Judith; Garrido, Antonio; De la Fuente, Mónica (Biogerontology (Dordrecht), 2025)
Homeostatic systems (nervous, immune, and endocrine) are crucial for maintaining health throughout life and, consequently, relevant for the rate of aging and the longevity achieved. In many species, male and female mammals show different lifespans, attributed to distinct redox states, but it is scarcely known whether sex differences in the functioning of these systems are involved. This study investigated, in an integrative view, sex differences in the nervous and immune systems of Swiss strain mice by analyzing behavior, immune function, and redox biomarkers across aging, to determine whether possible sex differences in homeostatic systems affect longevity. A longitudinal study was conducted on 20 female and male Swiss mice. At their young (2 mon), adult (7 mon), and old (18 mon) ages, subjects were subjected to a battery of behavioral tests, and peritoneal leukocytes were extracted to assess immune function and redox biomarkers. The natural deaths of animals were recorded for a longevity study. Our results indicate that sexual differences begin at a young age, and several are maintained until old age. Females, in general, show better behavior, immune function, and redox biomarkers, contributing to their higher longevity compared to males. The enhanced longevity in females may be attributable, in part, to the preservation of robust immune competence, with emphasis on innate immune functions and lower oxidative stress. The integration of behavioral and immunological profiles, together with redox biomarkers, underscores the critical importance of incorporating both sex as a biological variable in the design of aging-related research.